COMMUNICATIONAL SOURCES USED BY THE AGRICULTURAL AGENT TO TRANSFER AGRICULTURAL INFROMATION FOR RICE FARMERS IN AL-ABBASSIA / NAJAF Al-ASHRAF GOVERNORATE - Al-Salhi, A. T. Hd. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The research aimed to know the communicational sources used by agricultural Agent to transfer agricultural information for rice farmers in AL- Abbbassia of Najaf Al- Ashraf province and determine the most important extension means and method used by the agent in his contact with farmers. A questionnaire is designed to collect data included three scales to measure communicational sources (personal methods , collective methods, and mass media methoda ), The research community was farmers associations in AL-Abbassia cultivation section (11) association, The sample was farmers associations (36%) which were ( AL-Sadr, Iraq, Murtatha, and mohamed massage ), then another proportional random classical sample was taken (15%) of farmers of the mentioned associations (709) which was (106) farmers ,The research results showed that the communicational sources play a very important role in transfer of agricultural information to rice farmers, as well as the collective methods were most methods the used by extension agent to transfer the information, There were also some differences in the used sources which means that all methods were important. The research recommended to take care and attention to rice crop as a strategically crops, cooperation with general corporation of the agricultural research department of rice growing development , Inaddition it can recommended to support the research extension agents and rice farmers by training courses according to their communicational need.